Organic acids composition of Cydonia oblonga Miller leaf - Oliveira, Andreia P. (2008)
Organic acid profiles of 36 Cydonia oblonga Miller leaf samples, from three different geographical origins of northern (Bragança and Carrazeda de Ansiães) and central Portugal (Covilhã), harvested in three collection months (June, August and October of 2006), were determined by HPLC/UV (214 nm). Quince leaves presented a common organic acid profile, composed of six constituents: oxalic, citric, malic, quinic, shikimic and fumaric acids. C. oblonga leaves total organic acid content varied from 1.6 to 25.8 g/kg dry matter (mean value of 10.5 g/kg dry matter). Quinic acid was the major compound (72.2%), followed by citric acid (13.6%). Significant differences were found in malic and quinic acids relative abundances and total organic acid contents according to collection time, which indicates a possible use of these compounds as maturity markers. Between June and August seems to be the best period to harvest quince leaves for preparation of decoctions or infusions, since organic acids total content is higher in this season.